2014
DOI: 10.1103/physrevc.89.031302
|View full text |Cite
|
Sign up to set email alerts
|

Isospin nonconserving interaction in theT=1analogue states of the mass-70 region

Abstract: Mirror energy differences (MED) and triplet energy differences (TED) in the T = 1 analogue states are important probes of isospin-symmetry breaking. Inspired by the recent spectroscopic data of 66 Se, we investigate these quantities for A = 66 − 78 nuclei with large-scale shell-model calculations. For the first time, we find clear evidences suggesting that the isospin nonconserving (INC) nuclear force has a significant effect for the upper f p shell region. Detailed analysis shows that in addition to the INC f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
66
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 47 publications
7
66
1
Order By: Relevance
“…The latter is derived from the realistic Bonn-C nucleon-nucleon potential and a Linear Combination fit [68] to 400 experimental energies of 69 nuclei with A = 63 − 96. Both interactions have successfully been used to describe the nuclear properties of N ≈ Z nuclei in the A = 64 − 80 mass region [32,66,67]. In the present calculations, the effective charges for proton and neutron have been taken as e p = 1.5e and e n = 0.5e, respectively, which provide a good agreement with the observed B(E2) values in A ∼ 70 nuclei [69,70].…”
Section: B Comparison With Shell-model Calculationssupporting
confidence: 73%
See 1 more Smart Citation
“…The latter is derived from the realistic Bonn-C nucleon-nucleon potential and a Linear Combination fit [68] to 400 experimental energies of 69 nuclei with A = 63 − 96. Both interactions have successfully been used to describe the nuclear properties of N ≈ Z nuclei in the A = 64 − 80 mass region [32,66,67]. In the present calculations, the effective charges for proton and neutron have been taken as e p = 1.5e and e n = 0.5e, respectively, which provide a good agreement with the observed B(E2) values in A ∼ 70 nuclei [69,70].…”
Section: B Comparison With Shell-model Calculationssupporting
confidence: 73%
“…Both the effective interactions PMMU [32] and JUN45 [67] have been employed. The former is based on the unified realistic shell-model Hamiltonian PMMU [66], which includes the pairingplus-multipole Hamiltonian and a monopole interaction extracted from empirical fits starting from the monopolebased universal force. The latter is derived from the realistic Bonn-C nucleon-nucleon potential and a Linear Combination fit [68] to 400 experimental energies of 69 nuclei with A = 63 − 96.…”
Section: B Comparison With Shell-model Calculationsmentioning
confidence: 99%
“…[26]. It has been shown [5] that the multipole, monopole, and spin-orbit forces are not sufficient to explain the experimental TED for A = 66 and that the INC force is important for reproducing the observed experimental data [2]. The INC force used in the present calculation comprises an isotensor strength of 100 keV for J = 0 couplings for all the orbitals included in the model space, which is consistent with that required to reproduce the empirical TED of the A = 42 triplet in the f 7/2 shell [27].…”
mentioning
confidence: 99%
“…It is of high interest to extend such studies to higher masses, where the structure of the low-spin states involved is very different, evolving from dominance by fp orbitals to g 9/2 orbitals by A = 74 [4]. Moreover, predictions for the TEDs already exist with and without the INC component [5]. Irrespective of the techniques employed, however, the study of exotic proton-rich nuclei is challenging due to their low production cross sections.…”
mentioning
confidence: 99%
“…However, the nucleon-nucleon scattering data suggested that v nn is slightly more attractive than v pp , and v np is stronger than (v nn + v pp )/2 [4,5]. In real nuclear systems where manybody effects are important [6], isospin symmetry breaking has long been an active research theme connected to different subfields, for examples, in understanding the precise values of the Cabbibo-Kobayashi-Maskawa (CKM) mixing matrix elements between the u and d quarks [7,8], the changes in nuclear structure near the N = Z line due to charge-violating nuclear force [9][10][11][12], and the influence in nova nucleosynthesis [13]. …”
mentioning
confidence: 99%